ANHYDROUS PARTIAL MELTING OF PERIDOTITE FROM 8 TO 35 KB AND THE PETROGENESIS OF MORB - Falloon T.J.; Green D.H. (My University, 1988)
Equilibrium partial melts under anhydrous conditions have been determined for a MORB pyrolite composition (considered suitable for the production of primary MORB melts) from 8 to 35 kb and a relatively more depleted peridotite composition, Tinaquillo lherzolite, at 15 and 20 kb. The equilibrium partial melts were determined using ‘sandwich’ experiments. The primitive MORB glass DSDP3-18-7-1 was used in experiments using MORB pyrolite while a calculated liquid composition from Jacques & Green (1980) was used in experiments with Tinaquillo lherzolite. The equilibrium partial melts in conjunction with previous studies are used to establish a melting grid from 5 to 35 kb in the CIPW normative basalt tetrahedron. Equilibrium partial melts from MORB pyrolite combined with constraints imposed by the composition of primitive MORB glasses, MORB picrites and primitive trapped glass inclusions are subjected to olivine fractionation calculations to establish the range in composition of primary MORB melts. The results suggest primary MORB melts segregate from MORB source diapirs at pressures of 8 to 25kb in equilibrium with either lherzolite or harzburgite residues. MgO contents of primary MORB melts range from 10–17 wt.% while primary melts with > 17 wt.% MgO are of minor importance. Primary MORB melts range in composition from slightly ne-normative and more hy-normative picrites to olivine and quartz normative olivine tholeiite. Although some primitive MORB glass compositions are possible primary melts from 8–20 kb the majority of primitive MORB glass compositions are derived by olivine fractionation (11–25 wt.%) from more picritic parents from pressures of 15–25kb. The results of this study are in agreement with previous workers suggesting that there is an array of primary MORB melt compositions which evolve to multiple saturation in olivine+ plagioclase + clinopyroxene at different points along a latm. cotectic via differing degrees of olivine fractionation.